Politik Identitas Etnis Tionghoa di Kota Medan - MAGHFIRA FARAIDIANY (Universitas Sumatera Utara, 2016)
This study describes the political identity of the ethnic Chinese inMedan. As one of the largest ethnic group, this ethnic performs an essential role in the political life in Kota Medan. Theory of identity politics explain how Chinese people participate in politics through political identity and ethnicity as to promote ethnic unity. This study found there are three interesting phenomenonrelating to the identity of ethnic Chinese in Medan. First, the identity of the ethnic Chinese in Medan city is constantly changing; Secondly, the increasing number of Chinese ethnic community actively participates in political life; Third, the ethnic Chinese are considered to have an exclusive social life.These findings are based on qualitativedata. The approach used in this study is political behavior. Data was collected by interview and literature study. Informants in this study are members of several Chinese organizations, namely the Association INTI (Chinese Indonesian) and PSMTI (Paguyuban SosialMarga Tionghoa Indonesia ) as well as informants who come from political parties (Perindo). Keywords: Political Identity, Ethnicity, political participation.